Stories From Shakespeare : The Comedy Of Errors - Joseph, Mary (Sterling Publishers Private Ltd, 2004)
At last a Shakespeare series that bring to children from ten upwards all the exciting drama and magic of the originals.
Keywords: Tales / Legend - Shakespeare